Ethnobotanical Study of the Mexican Laurel in El Chico National Park, Mexico: A Quantitative Perspective - Daniela Ortega-Meza; María Teresa Pulido-Silva; Joari Costa de Arruda; Carolina Joana da Silva (Ethnobiology Letters, 2019)
This study was conducted in two villages of El Chico National Park (ECNP), Mexico, to document the uses of Litsea glaucescens (Mexican laurel) by the local population and to identify actors with knowledge about the species using quantitative ethnobotanical techniques. Fifty-five semi-structured interviews were conducted to obtain a free-list about the specific uses of the laurel, to analyze its importance among the social group under study, and to use social networking to identify individuals within the community who had particular knowledge about the plant. We found a total of 25 specific uses for the plant, which have different levels of importance for the people of the ECNP. The most common use was seasoning, while medicinal and cultural uses had a lesser importance. Use of the seed of the laurel as a material for handcrafts is recorded for the first time in this study. The social network showed that there was a relationship between the actors interviewed from the two communities. They are identified as having some relationship to the plant or knowledge about it, but the actors who produce it are the most prominent. An analysis of the specific uses of the laurel and those with knowledge about it is considered indispensable for generating specific management and harvesting strategies for the species, which will be able to contribute a local perspective to its conservation.